2009
DOI: 10.1159/000218199
|View full text |Cite
|
Sign up to set email alerts
|

Extraoperative Functional Mapping and Staged Resection of Supratentorial Tumors near Eloquent Cortex in Children

Abstract: We present our technique for extraoperative functional mapping in awake children with supratentorial tumors near eloquent cortex. This technique may help optimize tumor resection and/or the functional outcome, especially when an awake craniotomy is not possible or in the setting of coincident seizures. After subdural electrode implantation, extraoperative functional mapping and seizure focus mapping were performed, followed by staged tumor resection. Gross total resection was achieved in 6 patients and subtota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Our previous study reported that general anesthesia reduced the rate of interictal epileptiform discharges in a majority of patients with focal epilepsy who exhibited frequent interictal spiking during extraoperative recording [52]. Also, not many children with epilepsy can tolerate awake craniotomy for intraoperative functional language mapping [53]. The disadvantages of extraoperative ECoG monitoring include: (i) a requirement for a second craniotomy, (ii) greater financial cost, and (iii) increased risk of complications, including infection [54].…”
Section: Role Of Ecog Monitoringmentioning
confidence: 99%
“…Our previous study reported that general anesthesia reduced the rate of interictal epileptiform discharges in a majority of patients with focal epilepsy who exhibited frequent interictal spiking during extraoperative recording [52]. Also, not many children with epilepsy can tolerate awake craniotomy for intraoperative functional language mapping [53]. The disadvantages of extraoperative ECoG monitoring include: (i) a requirement for a second craniotomy, (ii) greater financial cost, and (iii) increased risk of complications, including infection [54].…”
Section: Role Of Ecog Monitoringmentioning
confidence: 99%
“…Invasive monitoring (IM) includes placement of subdural strips, grids, and, in certain cases, depth electrodes. IM directly records EEG activity from suspected brain areas, enabling direct mapping of epileptic networks, as well as functional mapping (Bollo et al., 2009). IM is critical when evaluating patients with multifocal epilepsy (Bauman et al., 2008, Carlson et al, 2011.…”
mentioning
confidence: 99%
“…Our center has considerable experience with the use of image guided (navigation and ultrasound) resections aided by neuromonitoring and extra-operative functional mapping [7,2,5] utilizing surface and depth electrodes. This approach serves as an effective alternative in younger children [4] who may be less likely to cooperate with an awake procedure.…”
Section: Discussionmentioning
confidence: 99%